DEPENDENCE OF THE THICKNESS OF RAW SILK ON THE REGULATION METHOD, THE PERIOD OF COMPENSATION OF ROSES AND THE SPEED OF UNWINDING OF COCOONS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The article studied the dependence of the thickness of raw silk on the control method, the rose compensation period and the speed of unwinding of cocoons and revealed that an increase in the rose compensation period leads to a slight increase in linear density and an increase in the square deviation. When controlling the linear density with the number of cocoons, it was noticed that the proportion (%) of the coefficient of variation in the thickness of raw silk, depending on the unevenness of the cocoon threads, decreases with increasing speed.